2016
DOI: 10.1080/17470218.2015.1063675
|View full text |Cite
|
Sign up to set email alerts
|

Negation in context: Evidence from the visual world paradigm

Abstract: Literature assumes that negation is more difficult to understand than affirmation, but this might depend on the pragmatic context. The goal of this paper is to show that pragmatic knowledge modulates the unfolding processing of negation due to the previous activation of the negated situation. To test this, we used the visual world paradigm. In this task, we presented affirmative (e.g., her dad was rich) and negative sentences (e.g., her dad was not poor) while viewing two images of the affirmed and denied enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…ERP studies of negation have focused on the N400 component, and have typically presented 49/67 more varied sentences reliant on long-term 'world knowledge ' (e.g., Fischler et al, 1983;Kounios & Holcomb, 1992;Nieuwland & Kuperberg, 2008). Eye-tracking studies of negation (e.g., Orenes et al, 2014;Orenes, Moxey, Scheepers, & Santamaría, 2016) make use of the visual world paradigm; this approach requires visual information to be presented concurrently with linguistic input, and hence does not directly involve memory. Our study sits in between these methodologies, as the tasks we have employed rely on the application of newly-acquired, contextually-relevant knowledge stored in short-term memory.…”
Section: /67mentioning
confidence: 99%
“…ERP studies of negation have focused on the N400 component, and have typically presented 49/67 more varied sentences reliant on long-term 'world knowledge ' (e.g., Fischler et al, 1983;Kounios & Holcomb, 1992;Nieuwland & Kuperberg, 2008). Eye-tracking studies of negation (e.g., Orenes et al, 2014;Orenes, Moxey, Scheepers, & Santamaría, 2016) make use of the visual world paradigm; this approach requires visual information to be presented concurrently with linguistic input, and hence does not directly involve memory. Our study sits in between these methodologies, as the tasks we have employed rely on the application of newly-acquired, contextually-relevant knowledge stored in short-term memory.…”
Section: /67mentioning
confidence: 99%
“…in the political context [8], in the context of prohibitive signs [9], in research on questions and negation as tools of insinuation [10], and in studies on mental control mechanisms [11]. However, it is also important to underline that in the last several years a large of amount research has shown that a delay in negation processing can be alleviated by pragmatics and different semantic contexts [12, 13,14,15,16,17,18]. The context in which the negation occurs may play a primary role in children’s (2–5 years) comprehension of negation [19].…”
Section: Introductionmentioning
confidence: 99%
“…It appears in all human languages, although it does not have the same grammar structure in all of them (Khemlani et al, 2012). Its importance is evidenced by the attention received from various disciplines, especially in the study of propositional reasoning (Macbeth et al, 2013;Macbeth, Razumiejczyk, Crivello, Fioramonti, & Pereyra-Girardi, 2015;Orenes et al, 2016).…”
Section: The Theory Of Negationmentioning
confidence: 99%
“…This phenomenon, easily explained by mathematical logic (Macbeth, Crivello, Fioramonti, Razumiejczyk, 2017a), nevertheless presents some difficulties when processed by the human mind. Some approaches tried to account for this complexity and proposed the intervention of pragmatic (Horn, 1989;Horn & Ward, 2005;Orenes, Moxey, Scheepers, & Santamaría, 2016), contextual (Sperber & Wilson, 1986;Wilson & Sperber, 1994) and conversational (Bott & Noveck, 2004;Grice, 1989) factors. Despite these efforts, it was not however until the proposal of Johnson-Laird (2012, 2014) that a complete Theory of Negation was presented.…”
Section: Introductionmentioning
confidence: 99%